Frontal White Matter Hyperintensities Effect on Default Mode Network Connectivity in Acute Mild Traumatic Brain Injury - Zhang, Danbin; Zhu, Pingyi; Yin, Bo; Zhao, Pinghui; Wang, Shan; Ye, Limei; Bai, Lijun; Yan, Zhihan; Bai, Guanghui (Frontiers in Aging Neuroscience, 2022)
The functional connectivity of the brain depends not only on the structural integrity of the cortex but also on the white matter pathways between cortical areas. White matter hyperintensities (WMH), caused by chronic hypoperfusion in the white matter, play a role in the outcome of traumatic brain injury (TBI) and other neurodegenerative disorders. Herein, we investigate how the location and volume of WMH affect the default-mode network (DMN) connectivity in acute mild TBI (mTBI) patients. Forty-six patients with acute mTBI and 46 matched healthy controls were enrolled in the study. All participants underwent T2-weighted fluid-attenuated inversion recovery magnetic resonance imaging (MRI), resting-state functional MRI (fMRI),and neuropsychological assessments. The volume and location of WMH were recorded. The relationships between the WMH volume and clinical assessments were evaluated using Spearman’s correlation. Patients with higher frontal lobe WMH volume had more severe post-concussion symptoms and poorer information processing speed. Moreover, these patients had significantly lower functional connectivity in the right middle temporal gyrus, left middle frontal gyrus, right superior frontal gyrus, and left anterior cingulate cortex, compared with patients with low frontal lobe WMH volume. Compared to the controls, the patients with high frontal WMH volume exhibited significantly lower functional connectivity in the right inferior temporal gyrus, left anterior cingulate cortex, and right superior frontal gyrus. These findings suggest that frontal lobe WMH volume may modulate the functional connectivity within the DMN. Therefore, the WMH volume in specific regions of the brain, particularly the frontal and parietal lobes, may accelerate the process of aging and cognitive impairment may be a useful biomarker for the diagnosis and prognosis of acute mTBI.